Sanitasi dan Higiene Penjamah serta Kandungan Jamur Aspergillus Flavus pada Saus Tomat Dagangan Bakso di Kecamatan Oebobo, Kota Kupang - Akmardan Rupawani Yewang; Sigit Purnawan; Marselinus Laga Nur (Media Kesehatan Masyarakat, 2022)
Sanitation and personal hygiene in the preparation and distribution of food are essential to food traders in order to avoid causing the contamination of microorganisms in food. One cause of food insecurity is the contamination of food with toxins produced by the fungus Aspergillus flavus. Meatballs are a popular food in the Indonesian community and are always served together with tomato sauce. Those who often pay no attention to personal hygiene, merchandise, tools, and their surroundings can potentially be contaminated by the fungus Aspergillus flavus. The study was to identify the sanitation and personal hygiene of the workers and the properties of the fungus Aspergillus flavus on the meaty tomato sauce used in the Oebobo District of Kupang City. This study aims to determine the description of the sanitation and personal hygiene of the handlers and the content of Aspergillus flavus in tomato sauce for meatball trade in Oebobo District, Kupang City. This study used a descriptive research method with a cross-sectional design. The sample of this study consisted of 10 meatball traders and 10 tomato sauce for meatball merchants in Oebobo District, Kupang City. The results of the study most of the respondents had poor hygiene, namely 5 respondents. A total of 4 respondents had good sanitation equipment and 4 respondents had poor sanitation in the premises. From the results of laboratory tests, there were 2 samples of tomato sauce containing the fungus Aspergillus flavus. The conclusion from the results of this study there were 2 positive samples of the Aspergillus flavus fungus. This is most likely because the two respondents have poor hygiene, equipment sanitation, and sanitary premises that do not meet health requirements.